On molecular statics simulation of ferroelectric barium titanate - Endres, Florian; Steinmann, Paul (Special Issue: 84th Annual Meeting of the International Association of Applied Mathematics and Mechanics, 2013)
The present contribution deals with the atomistic modelling of ferroelectric barium titanate. In this context a core-shell model is implemented in a Molecular Static algorithm. Furthermore, Coulomb forces are simulated by the Wolf summation method in order to allow for a small cut off radius. We discuss the core-shell model, molecular statics as a finite elements approach and present some numerical results.